A 5 year retrospective study of emergency department use in Northwest Ontario: a measure of mental health and addictions needs. Issue 5 (7th November 2016) - Matsumoto, Cai-lei; O'Driscoll, Terry; Lawrance, Jennifer; Jakubow, Andre; Madden, Sharen; Kelly, Len
Abstract: Objective: The main objective of this study was to understand the five-year trend in total emergency department (ED) visits, frequency of use, and diagnoses and disposition of patients. Since the region has experienced a profound increase in opioid use disorder since 2009, we were particularly interested in changes in the volume of mental health and addiction (MHA) ED presentations. Methods: Retrospective aggregate data analysis of ED visits to the Sioux Lookout Meno Ya Win Health Centre 2010-2014. Results: ED visit volume increased 29% over the five-year study period, while MHA ED visits increased 73%. The admission rate remained stable at 6.9% of ED visits. Five-year trends in clinically grouped diagnostic categories identified respiratory, MHA, and abdominal/pelvic complaints as the three most common ED presentations. In 2014, MHA presentations accounted for 10.3% of ED visits, 8.7% of admissions, and 20.0% of inter-hospital transfers. Conclusion: The dramatic increase in MHA ED visits mirrors the opioid epidemic the region is experiencing. MHA may soon become the commonest ED presentation. If reasons for ED visits serve as a proxy for unmet outpatient needs, increased efforts at developing community MHA services and addressing the related social determinants of health are required. Résumé: Objectif: L'étude décrite ici visait principalement à comprendre les tendances dégagées de statistiques recueillies sur une période de cinq ans quant au nombre total de consultations au service des urgences (SU), à la fréquence d'utilisation du service et des diagnostics ainsi qu'aux suites à donner. Compte tenu du fait que la région a connu une forte augmentation des problèmes liés à la consommation d'opioïdes depuis 2009, les changements quant au nombre de consultations au SU pour des troubles de santé mentale et de toxicomanie (SMT) intéressaient tout particulièrement les auteurs. Méthode: Il s'agit d'une analyse rétrospective de données agrégées sur les consultations médicales au SU du Sioux Lookout Meno Ya Win Health Centre, recueillies de 2010 à 2014. Résultats: Le nombre de consultations au SU a augmenté de 29 % durant la période à l'étude, et le nombre de consultations au SU pour des troubles de SMT, lui, a augmenté de 73 %. Par contre, le taux d'hospitalisation est resté stable, à 6, 9 % des consultations au SU. Les problèmes respiratoires, les troubles de SMT ainsi que les problèmes abdominaux ou pelviens se sont révélés les trois principaux groupes de diagnostics cliniques qui se sont dégagés des données recueillies sur la période de cinq ans. En 2014, les troubles de SMT représentaient 10, 3 % des consultations au SU, 8, 7 % des hospitalisations et 20, 0 % des mutations interhospitalières. Conclusions: L'augmentation considérable du nombre de consultations au SU pour des troubles de SMT reflète les proportions épidémiques que prend la consommation d'opioïdes dans la région. Les troubles de SMT pourraient bientôt devenir le principal motif de consultation au SU. Si les motifs de consultation au SU servent de déversoir de besoins non satisfaits parmi les patients externes, il faudra déployer davantage d'efforts pour mettre sur pied des services communautaires en santé mentale et en toxicomanie, et se pencher sur les déterminants sociaux connexes, liés à la santé.